PREVALENCE OF TRUANCY AMONG SECONDARY SCHOOL STUDENTS OF NAGAON TOWN OF ASSAM (International Journal of Food and Nutritional Sciences, 2022)
Defining Truancy Neumeyer (1955) cites the California Educational Code, which define truant as, “any child, between ages 8 to 15, who has been absent from school without valid cause more than three days or tardy more than three days”. Similarly, Tyerman (1955) defined “Truancy are children who absent from school without lawful cause and without permission of parents. Their non- attendance is due chiefly their own initiative, and for purposes of study they must be distinguished from those children whose parents are directly responsible for their absences, by holding them from school usually to help in the house”. But in certain cause it is difficult to determine whether the child is a truant or whether the parents have condoned their absence. Sometimes parental supervision may be weak accompanied by apathy and so marked as to constitute connivance.